Edukasi Kesehatan Mengenai Tonsilitis Pada Pasien Poliklinik THT di RSUD Provinsi NTB - Yuliyani, Eka Arie; yudhanto, Didit; Kadriyan, Hamsu; Wedayani, Anak Agung Ayu Niti; Resti, Nimas; Rahmansyah, Nafatasya Ayu; Romadoni, Muhammad Aulia Hikmah (Universitas Mataram, 2025)
Tonsillitis is a disease that is often found in society and can affect all age groups. However, the most common occurrence is in the children's. Tonsillitis can occur acutely, chronically or chronic acute exacerbation, depending on the duration and frequency of infection. The prevalence of tonsillitis globally shows a fairly high number, especially in developing countries. There are several risk factors that play a role in the high prevalence of tonsillitis in Indonesia including air pollution, poor sanitation, and exposure to infection in dense environments. Public awareness is considered lacking in early detection and treatment of tonsillitis often causes delays in treatment. The purpose of this health education is to provide understanding and increase the knowledge of the community visiting the polyclinic at the NTB Provincial Hospital regarding tonsillitis, its risk factors, symptoms, and how to prevent it. In this educational activity, participants were very enthusiastic about following each explanation of the material presented. Some of the education participants also asked questions about tonsillitis and its complications during the discussion session.This can be used as a benchmark as well as a reference and evaluation material for implementing similar activities in the future.